The antecedents of brand experience and its effect on trust and resonance: an empirical study of fast food industry in Malaysia / Rozita Naina Mohamed and Norzaidi Mohd Daud - Naina Mohamed, Rozita; Mohd Daud, Norzaidi (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
Notably, brand experience is still new and emerging. However, the antecedent’s influence of brand experience is still elusive. This study examined the antecedents influence of customers brand experiences and the consequences of trust on resonance of the four prominent fast food in Malaysia namely, Me Donald’s, Kentucky Fried Chicken, Pizza Hut and Kenny Rogers. Questionnaires were distributed to 400 respondents using quota sampling. Descriptive analysis was used to determine the perception of adult’s customers and Structural Equation Modelling (SEM) was utilized to determine the significant levels of associations and interactions between the variables tested. The result of this study will provide insights into the brand experience factors that could influence successful implementation of branding models specifically for the fast food industry and academicians’ purposes. Indeed, it could also unveil the opportunity for the fast food businesses to reformulate their branding strategies to increase its revenue and earnings thereby ensuring corporate longevity in today’s competitive environment